Investigation of Crushed Aggregate as Stemming Material in Bench Blasting: A Case Study - Sharma S.K.; Rai P. (My University, 2025)
The present paper summarizes the application of two different types of stemming material used in bench blasting. The two stemming material types, namely crushed aggregate and drill cuttings were opted in the present study. The blast trials were conducted on overburden rocks of Garnet Biotite Sillimanite Gneiss (GBSG) formations in one of the largest metalliferous mines of India. These rocks were exposed to polyphase deformations, high-grade metamorphism that comprised of various fissures, joints and foliation planes. An attempt was made through this paper to assess the influence of aggregate stemming material on blasting results. The study revealed that the quality of stemming material significantly influences the blasting performance in moderately strong (UCS 45 MPa) blasting benches of GBSG formations. Hence, the quality of stemming material must be considered in designing blast rounds in such overburden rock formations to achieve production targets. The results were assessed by fragment size measurement in the blasted muck-piles using image analysis technique, excavator performance anticipated by digging rate and muck-pile shape parameters. The fragment size and its distribution affected the digging rate of excavators. The use of crushed aggregate stemming material yielded better fragmentation results in comparison to the drill cuttings in such overburden rock formations. The average fragment size (K50) values for blasts stemmed with drill cuttings were (0.58–0.77 m) higher than that of blasts stemmed with crushed aggregate stemming material (0.45–0.59 m). The digging rate of shovels (34 m3) per hour was consistent and about 18 % higher in blasts stemmed with crushed aggregate stemming material. Muck-pile resulting from every blast was surveyed and throw distance was measured. The average muck-pile throw were 21.2 % higher in blasts stemmed with drill cutting stemming material. Whereas vertical cratering was higher in blasts stemmed with crushed aggregate stemming material. © 2015, Springer International Publishing Switzerland.